On The Use Of Nano Fibrillated Kenaf Cellulose Fiber As Reinforcement In Polylactic Acid Biocomposites - Ahsan, Qumrul (Universiti Malaysia Pahang, Malaysia, 2019)
In this study, nano fibrillated kenaf cellulose (NFKC) derived from kenaf fiber after varying chemico-mechanical treatments were introduced into poly lactic acid (PLA) as reinforcements to improve the mechanical and morphological properties of the biocomposites. The new strategy was aiming to realize the synergistic effects of chemical treatment and mechanical fibrillation process parameters (blending speed and time) for yielding nanofibers and its reinforcement effects on the properties of biocomposites. The yield percentage of the NFKC was determined using centrifugal method and the NFKC fibers with PLA pellet were hot pressed to form NFKC-PLA composites. The distribution and dispersion morphologies of NFKC in NFKC-PLA composites were observed by using optical microscope (OM) and scanning electron microscope (SEM). The reinforcing effect on the mechanical properties of NFKC-PLA composite was investigated by tensile strength test. Average length and diameter of fibrillated fibers were decreased with the concurrent increase of blending speed and time. The maximum increase in tensile strength of 59.32% and elongation of 100% were observed for NFKC-PLA composite with NFKC yielded at a blending speed and time of 15000 rpm and 15 minutes as compared to pure PLA. The tensile properties indicated that the strength and modulus were improved with increased nanofiber contents.